PEMANFAATAN DAN PEMASARAN ROTAN OLEH MASYARAKAT KABUPATEN SAMOSIR (Studi Kasus di Desa Huta Galung, Kecamatan Harian, Kabupaten Samosir) - Ricky Situmorang; Ridwanti Batubara; Yunus Afifuddin (Program studi Kehutanan USU, 2013)
Rattan (Calamus sp) is a forest plant that has many benefits for forest communities and a source of foreign exchange. This study aims to known the utilization of rattan by the community, determine income from the use of rattan and non rattan and to analyzed the marketing of rattan. This research used field surveys and interview to the community. Based on research conducted known pattern rattan harvesting is done by rotation. Income from rattan smaller than non-rattan with the percentage utilization of rattan 43.8%, while non-rattan 56.20%. Marketing rattan starting from rattan farmers sell rattan to collector and collector which will sell directly to craftsmen. Keywords: Rattan, Income, Marketing